Conformal and Bilinear
Conformal and Bilinear
Conformal and Bilinear
BY
Assistant Professor
Department of Mathematics
University of Kalyani
West Bengal, India
E-mail : sahoopulak1@gmail.com
1
Module-2: Bilinear Transformation -
Basic Properties
az + b
w = f (z) = (1)
cz + d
a b
where = ad − bc 6= 0 is called a Bilinear Transformation or Möbius Transforma-
c d
tion or linear fractional transformation. The expression ad − bc is called the determinant
of the transformation.
Azw + Bz + Cw + D = 0, AD − BC 6= 0.
Since this is linear in both the variables z and w, (1) deserves to be termed bilinear
transformation.
2
Theorem 1. The inverse of a bilinear transformation is also a bilinear transformation.
Proof. Let
az + b
w = , ad − bc 6= 0
cz + d
−dw + b
z = , (2)
cw − a
where the determinant of the transformation is ad−bc which is not zero. Thus the inverse
of a bilinear transformation is also a bilinear transformation.
Remark 2. From the bilinear transformation (1) and its inverse (2) it follows that to
every z other than z = −d/c (w has a simple pole at z = −d/c) there corresponds
only one value of w and to every value of w other than w = a/c (z has a simple pole at
w = a/c) corresponds just one value of z. We suppose that the point at infinity in the
w-plane corresponds to the point z = −d/c, and that the point at infinity in the z-plane
is mapped into the point w = a/c. Thus if c 6= 0, z = ∞ corresponds to w = a/c and
z = −d/c corresponds to w = ∞. When c = 0, the point z = ∞ corresponds to w = ∞.
Therefore, for c 6= 0, we have
az+b
cz+d
, if z 6= −d/c, z 6= ∞
w = f (z) = ∞, if z = −d/c
a
if z = ∞.
c
It now follows that the bilinear transformation (1) set up a one-one correspondence be-
tween the points of the extended z-plane and the points of the extended w-plane.
az+b
Proof. Let w = f (z) = cz+d
, ad − bc 6= 0 be a bilinear transformation. Then
a(cz + d) − c(az + b) ad − bc
f 0 (z) = = 6= 0 f or z 6= −d/c,
(cz + d)2 (cz + d)2
3
Proof. Let
a1 z + b1
ζ = , a 1 d 1 − b1 c1 =
6 0
c1 z + d1
a2 ζ + b2
and w = , a 2 d 2 − b2 c2 =6 0
c2 ζ + d2
a2 ac11z+d
z+b1
1
+ b2 (a1 a2 + b2 c1 )z + (a2 b1 + b2 d1 )
w = =
c2 ac11z+d
z+b1
1
+ d2 (a1 c2 + c1 d2 )z + (b1 c2 + d1 d2 )
az + b
= ,
cz + d
where a = a1 a2 + b2 c1 , b = a2 b1 + b2 d1 , c = a1 c2 + c1 d2 , d = b1 c2 + d1 d2 . Again
a b a1 b1 a2 b2
ad − bc = =
6= 0.
c d c1 d1 c2 d2
Proof. We have
1·z+0
w =z = ,
0·z+1
Proof. Let
a1 z + b1
T1 : ζ = , a1 d1 − b1 c1 6= 0,
c1 z + d1
a2 ζ + b2
T2 : λ = , a2 d2 − b2 c2 6= 0
c2 ζ + d 2
a3 λ + b3
and T3 : w = , a3 d3 − b3 c3 6= 0
c3 λ + d 3
4
Therefore,
Again
a3 ac22ζ+d
ζ+b2
2
+ b3
T3 T2 : w =
c3 ac22ζ+d
ζ+b2
2
+ d3
(a2 a3 + b3 c2 )ζ + (a3 b2 + b3 d2 )
= .
(a2 c3 + c2 d3 )ζ + (b2 c3 + d2 d3 )
So
(a2 a3 + b3 c2 ) ac11z+d
z+b1
1
+ (a3 b2 + b3 d2 )
(T3 T2 )T1 : w =
(a2 c3 + c2 d3 ) ac11z+d
z+b1
1
+ (b2 c3 + d2 d3 )
(a1 a2 a3 + a3 b2 c1 + a1 b3 c2 + b3 c1 d2 )z + (a2 a3 b1 + a3 b2 d1 + b1 b3 c2 + b3 d1 d2 )
=
(a1 a2 c3 + b2 c1 c3 + a1 c2 d3 + c1 d2 d3 )z + (a2 b1 c3 + b2 c3 d1 + b1 c2 d3 + d1 d2 d3 )
az + b
= .
cz + d
This shows that T3 (T2 T1 ) = (T3 T2 )T1 and so the associative property holds for the
composition of bilinear transformation.
z z−1
T1 (z) = ; T2 (z) = .
z+1 z−2
Therefore,
z−1 z−1
T1 T2 (z) = T1 (T2 (z)) = T1 = ,
z−2 2z − 3
z 1
T2 T1 (z) = T2 (T1 (z)) = T2 = .
z+1 z+2
Hence, T1 T2 (z) 6= T2 T1 (z). This shows that bilinear transformations do not satisfy the
commutative property.
5
Note 2. The set of all bilinear transformations form a non-commutative group with
respect to the composition of maps.
Theorem 6. Every bilinear transformation maps circles and lines into circles and lines
(a line is a circle of infinite radius).
az+b
Proof. Let w = f (z) = cz+d
, ad − bc 6= 0 be a bilinear transformation. If c = 0, then
a b a b
f (z) = z + = Az + B, A = and B = .
d d d d
Clearly, Az + B, being linear, maps circles and lines into circles and lines.
If c 6= 0, then
a
+ d) − ad
c
(cz c
+b
f (z) =
cz + d
a bc − ad 1
= + 2
· .
c c z + d/c
Assigning
1 bc − ad
z1 = z + d/c, z2 = , z3 = z2
z1 c2
a
we obtain f (z) = c
+ z3 . It is clear that the above transformations are of the form
1
w1 = z + α, w2 = , w3 = βz.
z
This establishes the fact that every bilinear transformation is the resultant of bilinear
transformations with simple geometric imports. Thus, a bilinear transformation maps
circles and lines into circles. This proves the theorem.
2z+3
Example 2. Show that the transformation w = z−4
maps the circle x2 + y 2 − 4x = 0
onto the line 4u + 3 = 0.
4w + 3
z = .
w−2
x2 + y 2 − 4x = 0
6
i.e. | z |2 −4Re z = 0
i.e. zz − 2(z + z) = 0.
Putting the value of z and noting that w = u + iv, we obtain from above
4w + 3 4w + 3 4w + 3 4w + 3
· −2 + =0
w−2 w−2 w−2 w−2
i.e. 2(w + w) + 3 = 0
i.e. 4u + 3 = 0,
Example 3. Show that the line x = 3y is mapped onto the circle under the bilinear
iz+2
transformation w = 4z+i
. Find the centre and radius of the image circle.
−iw + 2
z = .
4w − i
(v + 2) − iu
x + iy =
4u + i(4v − 1)
[(v + 2) − iu][4u − i(4v − 1)]
=
16u2 + (4v − 1)2
9u − i(4u2 + 4v 2 + 7v − 2)
= .
16u2 + (4v − 1)2
9u 4u2 + 4v 2 + 7v − 2
x = , y =− .
16u + (4v − 1)2
2 16u2 + (4v − 1)2
9u 4u2 + 4v 2 + 7v − 2
= −3
16u2 + (4v − 1)2 16u2 + (4v − 1)2
3 7 1
i.e. u2 + v 2 + u + v − = 0,
4 4 2
q
3 5
which represents a circle with centre at (−3/8, −7/8) and radius 4 2
.
7
Example 4. Find the image of the annulus {z : 1 <| z |< 2} under the bilinear
z
transformation w = 1−z
.
z
Solution. Here the transformation is w = 1−z
. Solving for z we obtain
w
z = .
1+w
Now